2011
DOI: 10.1136/sti.2010.046557
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the resources required in the roll-out of universal access to antiretroviral treatment in Zimbabwe

Abstract: ObjectivesTo develop projections of the resources required (person-years of drug supply and healthcare worker time) for universal access to antiretroviral treatment (ART) in Zimbabwe.MethodsA stochastic mathematical model of disease progression, diagnosis, clinical monitoring and survival in HIV infected individuals.FindingsThe number of patients receiving ART is determined by many factors, including the strategy of the ART programme (method of initiation, frequency of patient monitoring, ability to include pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…In particular, HBHTC allows achieving levels of HTC uptake that are considerably higher than those achieved through mobile clinics or facility-based HTC services (12). Our results also suggest that changing patterns of participation and HIV case-finding during repeated HBHTC campaigns should be incorporated in mathematical models used to estimate the potential effects of TasP on HIV incidence (4, 33, 34). Finally, they highlight the need for additional interventions to reach individuals who do not use HBHTC services even after multiple campaigns.…”
Section: Discussionmentioning
confidence: 76%
“…In particular, HBHTC allows achieving levels of HTC uptake that are considerably higher than those achieved through mobile clinics or facility-based HTC services (12). Our results also suggest that changing patterns of participation and HIV case-finding during repeated HBHTC campaigns should be incorporated in mathematical models used to estimate the potential effects of TasP on HIV incidence (4, 33, 34). Finally, they highlight the need for additional interventions to reach individuals who do not use HBHTC services even after multiple campaigns.…”
Section: Discussionmentioning
confidence: 76%
“…Condom use will continue to be emphasized as an adjunctive tool for HIV/STI risk reduction [292, 299, 300]. The biomathematics of combining methods for prevention are compelling, but intimidating at the same time; substantial coverage will be needed to succeed in bringing the basic reproductive rate to <1 thereby offering the potential prospect of eventual elimination of HIV as a public health problem [34, 301309, 310•, 311313]. …”
Section: Elements Of Combination Preventionmentioning
confidence: 99%
“…Estimates of life expectancies of HIV-infected individuals are important in providing information to patients about their long-term prognosis, in projecting the future costs of HIV-related care, and in forecasting the likely future demographic and socioeconomic impact of HIV/AIDS [1][3]. Several estimates of the life expectancy of HIV-positive adults in high-income countries have been published [4][13], and many of these studies have shown dramatic improvements in life expectancy following the introduction of highly active antiretroviral treatment (ART).…”
Section: Introductionmentioning
confidence: 99%